N-chelate ruthenium carbene complexes in olefin metathesis and isomerization; Russian Journal of Organic Chemistry; Vol. 51, iss. 7 - Shcheglova N. M. Nadezhda Mikhaylovna; Kolesnik V. D. Vasily Dmitrievich; Ashirov R. V. Roman Vitaljevich; Krasnokutskaya E. A . Elena Aleksandrovna (2015, 2015)
Title screen